Altered electrochemistry of amiloride drug on boron-doped diamond electrode: Rapid and selective detection in urine by square-wave cathodic stripping voltammetry for application in doping control. (20th March 2021) - Souza, Karla A.O.; Nunes, Ana M.F.; Pimentel, Dilton M.; Verly, Rodrigo M.; Gil, Eric S.; Malagutti, Andréa R.; dos Santos, Wallans T.P.
Abstract: The amiloride (AMI) is a diuretic drug and has been illegally used in sports competitions. The development of simpler and faster analytical methods for AMI determination in urine samples is of interest of the World Anti-Doping Agency (WADA). In this context, we present a novel electroanalytical method for selective and sensitive detection of AMI in urine samples using a boron-doped diamond electrode (BDDE) with square-wave cathodic stripping voltammetry (SWCSV). Additionally, for the first time, we propose a complete electrochemical mechanism for all (six) presented redox processes of AMI. The determination of AMI is based on one of its reduction processes at the BDDE at -0.3 V (vs Ag/AgCl), which allows the electrochemical detection of this drug in urine without interference from ascorbic and uric acids. The analytical performance of the proposed method provides a linear range of 0.5 to 55.1 μmol L   −   1 (r 2 =0.99) with LOD of 0.15 μmol L   −   1, which is sufficiently low to assess urine sample containing AMI in anti-doping testing. Furthermore, the recovery studies in human urine samples were around 100% with a good stability (RSD < 2.0%) of the electrochemical response for AMI detection at BDDE by SWCSV, suggesting its application as a simple and rapid screening method for doping control of this drug.